The interaction between dietary nitrates/nitrites intake and gut microbial metabolites on metabolic syndrome: a cross-sectional study - Mirzababaei, Atieh; Mahmoodi, Maryam; Keshtkar, Abbasali; Ebrahimi, Sara; Pashayee-Khamene, Fereshteh; Abaj, Faezeh; Radmehr, Mina; Khalili, Pardis; Mehri Hajmir, Mahya; Mirzaei, Khadijeh (Frontiers in Public Health, 2024)
Background: Metabolic syndrome (MetS) prevalence has increased globally.The evidence shows thatdiet and gut microbial metabolites includingtrimethylamine N-oxide (TMAO) and kynurenine (KYN) play an important role in developing MetS. However, there is a lack of evidence on associations between between diet and these metabolites. This study aimed to investigate the interaction between dietary nitrate/nitrite and gut microbial metabolites (TMAO, KYN) on MetS and its components. Methods: This cross-sectional study included 250 adults aged 20-50 years. Dietary intake was assessed using food frequency questionnaires (FFQ), and serum TMAO and KYN levels were measured. MetS was defined usingthe National Cholesterol Education Program Adult Treatment Panel (NCEP ATP III) criteria.The ATPIII index revealed an 11% prevalence of metabolic syndrome among the study participants .After adjusting for confounders, significant positive interactions were found: High animal-source nitrate intake and high TMAO levels with elevated triglycerides (TG) (p interaction = 0.07) and abdominal obesity (p interaction = 0.08).High animal-source nitrate intake and high KYN levels with increased TG (p interaction = 0.01) and decreased high-density lipoprotein cholesterol (HDL) (p interaction = 0.01).Individuals with high animal-source nitrite intake and high TMAO levels showed increased risk